Ilmu al-Jarḥ wa al-Ta’dil - Maulana Maulana (Refleksi: Jurnal Kajian Agama dan Filsafat, 2007)
In the study and research of hadith quality, the science of jarḥ and ta’dīl is one of the important ‘ulūm al-ḥadīth (sciences of hadith) that researchers need to possess. Mastery of this science is crucial for accurately determining whether the hadith under investigation is ultimately accepted (maqbūl) as a ḥujjah (a valid source for Islamic teachings) or rejected (mardūd), deemed unreliable. Hadith scholars have established classifications or degrees and levels of jarḥ, ta’dīl, and ḍabt (precision) for narrators of hadith. Their classifications are clearly evident in the expressions used, both in the statements of jarḥ and ta’dīl, as well as in the statements of ḍabt. This article provides a descriptive analysis of a highly valuable science for hadith research.